Organic carbon isotope record since the Late Glacial period from peat in the North Bank of the Yangtze River, China. (12th March 2021) - Zhou, Hui; Zhu, Cheng; Wu, Li; Zheng, Chaogui; Sun, Xiaoling; Guo, Qingchun; Lu, Shuguang
ABSTRACT: Detailed organic carbon isotope ( δ 13 Corg ) measurements were conducted on two peat sequences recovered from the north bank of the Yangtze River, East China. Seven radiocarbon dates provided firm age control of this δ 13 Corg record and reveal palaeoclimatic changes since the Late Glacial period. The results show that the Holocene Megathermal Maximum occurred between 8385 and 7040 cal. yr BP. The Late Glacial climate was generally cold but fluctuated frequently between 12940 and 11815 cal. yr BP. The Older Dryas (from 12940 to 12810 cal. yr BP) and the Younger Dryas (from 12645 to 12170 cal. yr BP) were characterised by cold climate conditions. In contrast, 12810 to 12645 cal. yr BP (corresponding to the Allerød Warm Period) and 12170 to 11815 cal. yr BP (corresponding to a rapid warming period after the Younger Dryas, marking the beginning of the Holocene) were relatively warm phases. In contrast to other high-resolution records, it shows that the δ 13 Corg records of our study peats are largely controlled by a common forcing mechanism of solar insolation changes in the Northern Hemisphere, and exhibit similar variability to δ 18 O records obtained from stalagmites and GISP2 during the Late Glacial and early-mid Holocene.